Financial Access Under the Microscope - Agarwal, Sumit (IMF Working Papers; Working Paper ;, 2018)
We examine the impact of a large-scale microcredit expansion program on financial access and the transition of previously unbanked borrowers to commercial banks. Using administrative micro-data covering the universe of loans to individuals from a developing country, we show that the program significantly increased access to credit, particularly in less developed areas. This effect is driven by the newly set-up credit cooperatives (U-SACCOs), which grant loans to previously unbanked individuals. A sizable share of first-time borrowers who need a second loan switch to commercial banks, which cream-skim low-risk borrowers and grant them larger, cheaper, and longer-term loans. These borrowers are not riskier than similar individuals already at commercial banks and only initially receive smaller loans. Our results suggest that the microfinance sector, together with a well-functioning credit reference bureau, help mitigate information frictions in credit markets.